Vegetation changes through stadial and interstadial stages of MIS 4 and MIS 3 based on a palynological analysis of the Girraween Lagoon sediments of Darwin, Australia - Rowe, Cassandra; Brand, Michael; Wurster, Christopher M.; Bird, Michael I. (Palaeogeography, palaeoclimatology, palaeoecology, 2024)
A palynological record from Girraween Lagoon sediments (Darwin region of the Northern Territory, Australia) provides detailed long-term insight into tropical savanna vegetation community patterns, climatic and fire relationships, through Marine Isotope Stage 4 (MIS 4: 71–57 thousand years ago, ka) and Marine Isotope Stage 3 (MIS 3: 57–29 ka). Owing to a lack of data in reconstructing northern Australian environments, this paper looks to define and describe to a greater degree the nature and scope of these stadial and interstadial stages for the region. Girraween Lagoon simultaneously provides proximal palaeoecological data for the time and region of Aboriginal people's first arrival into Australia, also encompassing the late Pleistocene continental decline of megafauna. This study provides a dataset enabling full exploration of long-term people-landscape and faunal-floral interactions. Sea levels and associated variations imposed on the transportation of moisture and heat, held implications for MIS 4 and MIS 3 monsoon strength, which was particularly consequential for Girraween regional ecology. Results reveal a prolonged transition from wooded- to grassy-savanna, into a cool drier semi-arid savanna. Increasingly episodic delivery of moisture influenced the permanency of freshwater in the landscape. •A detailed picture of vegetation in monsoonal north Australia during MIS 4 and MIS 3.•An ultimate transition from grassy eucalypt savanna into semi-arid savanna revealed.•Changed monsoonal delivery particularly consequential for regional ecology.•An indication of baseline landscapes during people's first arrival into Australia.•Assisting to place megafaunal decline within an ecological landscape.